Politique commerciale canadienne : d'un protectionnisme pragmatique au système de préférence britannique et à I'ALENA - Nyahoho, Emmanuel (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1996)
Canadian trade policy is largely one 0} compromise between the interests 0} Us main partners and a constant search for improved access to foreign markets. The establishment 0} GATT permitted the Canadian government to multilaterally pursue the principle of free trade on a basis of non-discrimination. Nevertheless, this policy 0} market diversification conflicted with three economic events, namely : entry of United Kingdom to the EEC, the breakdown of the Bretton Woods System, and the emergence of protectionism in the United States. Canada has decided to sign the FTA in 1989 with the United States, which now is extended to include Mexico. This regional block, similar to the EEC, does not signify the limits of a Worldwide utopia, but is very well a step toward market globalisation.